1996
DOI: 10.1002/hep.510230519
|View full text |Cite
|
Sign up to set email alerts
|

Absence of the canalicular isoform of the MRP gene-encoded conjugate export pump from the hepatocytes in Dubin-Johnson syndrome

Abstract: The Dubin-Johnson syndrome is characterized by an patocytes into the bile. 3,4 This defect results in predomiinherited defect in the secretion of amphiphilic anionic nantly conjugated hyperbilirubinemia and a characterconjugates from hepatocytes into the bile. We have re-istic secondary rise of intravenously administered cently identified the membrane protein mediating the sulfobromophthalein in blood plasma following its conadenosine triphosphate (ATP)-dependent transport of jugation with glutathione in hepat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(48 citation statements)
references
References 2 publications
2
46
0
Order By: Relevance
“…In spite of the similarity in substrate range, the functions of MRP2 in the body are distinct from those of MRP1 as a result of differences in expression pattern and subcellular polarity. In contrast to MRP1, MRP2 assumes apical localization in polarized cells (Figure 2), and it is mainly expressed in liver canaliculi, with lower levels in renal proximal tubules, gut enterocytes, syncytiotrophoblast cells of the placenta and possibly brain capillaries (Kartenbeck et al, 1996;Schaub et al, 1997;Miller et al, 2000;Mottino et al, 2000;St-Pierre et al, 2000). Therefore, it is functionally similar to Pgp in its involvement in the terminal elimination of compounds and its role as a barrier in gut and placenta.…”
Section: Mrp2mentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of the similarity in substrate range, the functions of MRP2 in the body are distinct from those of MRP1 as a result of differences in expression pattern and subcellular polarity. In contrast to MRP1, MRP2 assumes apical localization in polarized cells (Figure 2), and it is mainly expressed in liver canaliculi, with lower levels in renal proximal tubules, gut enterocytes, syncytiotrophoblast cells of the placenta and possibly brain capillaries (Kartenbeck et al, 1996;Schaub et al, 1997;Miller et al, 2000;Mottino et al, 2000;St-Pierre et al, 2000). Therefore, it is functionally similar to Pgp in its involvement in the terminal elimination of compounds and its role as a barrier in gut and placenta.…”
Section: Mrp2mentioning
confidence: 99%
“…Prior to the molecular identification of MRP2, several of its cardinal biochemical and physiological functions had been deduced from investigations of humans and rats that have since been determined to be genetically deficient in the pump (Kartenbeck et al, 1996;Paulusma et al, 1996). In older studies, the protein that is now known as MRP2 was often referred to as the canalicular multispecific organic anion transporter (cMOAT), a designation that aptly describes its ability to extrude a range of lipophilic anions into the bile.…”
Section: Mrp2mentioning
confidence: 99%
“…missense mutations in the ABCC2 gene cause conjugated hyperbilirubinemia (Dubin-Johnson syndrome) (13,14). Although a spectrum of mutations within the ABCC6 gene is clearly responsible for PXE, the functional relationship between altered ABCC6 gene expression and the PXE phenotype is still unknown.…”
Section: Pseudoxanthoma Elasticum (Pxe)mentioning
confidence: 99%
“…Furthermore, mutations in the ABCC2 gene resulting in the absence of the protein from the canalicular membrane have been described (33)(34)(35). Tirona et al have shown that polymorphisms in the SLC21A6 gene vary with respect to their frequency between the European-American and African-American population (18).…”
Section: Figmentioning
confidence: 99%